FDI, Trade and Economic Development in Pakistan - Muhammad Afzal; Shoaib Ahmad (Quantitative Economics and Management Studies, 2020)
This paper examined the relationship between FDI, imports, exports, terms of trade and investment in Pakistan for the period 1990-2015. Results show that an increase in all these factors will contribute significantly to FDI flows that may help the Pakistan’s economy. FDI has negative and significant impact on GDP. Exports have an insignificant effect that may imply that historically economy had led exports more than the exports led the economy. More important fact is that world economic conditions play a crucial role in the macroeconomic performance. When these conditions are favorable, not only the economy but also the trade grow. Though global financial crisis did not seriously affect Pakistan’s economy, Pakistan faced multifaceted challenges on external and internal fronts notably fight against extremism, energy crisis and uncertain external inflows. There is a need to pay more attention to domestic situation than to look abroad for financial assistance since FDI is not an unmixed blessing.